Carbon monoxide inhalation induces headache but no migraine in patients with migraine without aura. (November 2018) - Ghanizada, Hashmat; Arngrim, Nanna; Schytz, Henrik Winther; Olesen, Jes; Ashina, Messoud
Introduction: Carbon monoxide is an endogenously produced signaling gasotransmitter known to cause headache and vasodilation. We hypothesized that inhalation of carbon monoxide would induce migraine-like attacks in migraine without aura patients. Methods: In a randomized, double-blind, placebo-controlled crossover design, 12 migraine patients were allocated to inhalation of carbon monoxide (carboxyhemoglobin 22%) or placebo on two separate days. Headache and migraine characteristics were recorded during hospital (0–2 hours) and post-hospital (2–13 hours) phases. Results: Six patients (50%) developed migraine-like attacks after carbon monoxide compared to two after placebo (16.7%) ( p = 0.289). The median time to onset of migraine-like attacks after carbon monoxide inhalation was 7.5 h (range 3–12) compared to 11.5 h (range 11–12) after placebo. Nine out of 12 patients (75%) developed prolonged headache after carbon monoxide. The area under the curve for headache score (0–13 hours) was increased after carbon monoxide compared with placebo ( p = 0.033). Conclusion: Carbon monoxide inhalation did not provoke more migraine-like attacks in migraine patients compared to placebo, but induced more headache in patients compared to placebo. These data suggest that non-toxic concentrations of carbon monoxide had low potency in migraine induction and that the carbon monoxide inhalation model is not suitable to study migraine.